Analisis Kompetensi Aparatur dalam PerAnalisis Kompetensi Aparatur dalam Perencanaan dan Penganggaran yang Responsif Gender di Sumatera Utaraencanaan dan Penganggaran yang Responsif Gender di Sumatera Utara - Dr. Ir. Hj. Sabrina, M. Si Sabrina Sabrina (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
Gender mainstreaming in development is required with the issuance of various regulations. The implementation is carried out through Gender Responsive Planning and Budgeting (GRPB). This research aims to find out the competence of HR planners in implementing gender responsive planning and budgeting in North Sumatra regional development programs/activities. This research used qualitative, and the data used are primary data and secondary data. Primary data were collected through questionnaires and limited interviews with employees and head of department in the Regional Government Organization (RGO) of North Sumatra Province. Secondary data is obtained from relevant documents and references. The data were analyzed descriptively to obtain actual conditions/problems which were then used as the basis for the preparation of the GRPB Consulting Clinic design in order to increase the competence of human resource planners and improving the implementation of gender mainstreaming in the development of the North Sumatra region. From this case, it was found that the realization of GRPB in North Sumatra regional development programs/activities was still low and did not reach the target. This is due to the lack of commitment from the RGO leadership and the Regional GRPB Secretariat and the low competence (knowledge and skills/ability) of HR Planning in RGO regarding the GAP (Gender Analysis Pathway) and GBS (Gender Budget Statement) techniques as GRPB analysis tools. To advance the competence of the planning human resources, it is necessary to operate a GRPB Consulting Clinic which can be contacted every day, with the following tasks/activities: providing consultation on GRPB, namely knowledge and skills regarding Gender Analysis Pathway (GAP) and Gender Budget Statement (GBS) techniques, as well as increasing the quantity and the quality of filling out GAP and GBS forms for development programs/activities. Keywords: Apparatus competence, Planning and Budgeting, Gender Responsive, GAP, GBS.